Current approaches to vision restoration using optogenetic therapy - Parnami, Kashish; Bhattacharyya, Anwesha (Frontiers in Cellular Neuroscience, 2023)
Inherited progressive degeneration of photoreceptors such as retinitis pigmentosa (RP) is the most common cause of blindness leading to severe vision impairment affecting 1 in 5,000 people worldwide. Although the function and morphology of the photoreceptors get disrupted, there is evidence that the inner retinal neurons such as bipolar cells and the retinal ganglion cells are left intact until later stages. Among several innovative therapeutic options aiming to restore vision, optogenetic therapy can bestow light sensitivity to remaining retinal neurons by ectopic expression of light-sensitive proteins. Since the advent of this technique, a diverse class of opsins (microbial and mammalian opsins), chimeric proteins, ligand-gated ion channels, and switchable opsins have been used to study their potential in vision restoration. These proteins differ in their excitation spectra, response kinetics, and signal amplification cascade. Although most of the studies have reported high fidelity of responses in the retina, only a handful of them have achieved functional vision in the visual cortex. This review is a summary of the visuocortical and behavioral responses after optogenetic treatment of the degenerated retina. This clarifies to what extent improved and meaningful vision can be obtained for therapeutic efficacy and continued clinical progress.